2005
DOI: 10.1021/ie048776m
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Surface Resistance in Absorption by Polymers

Abstract: Solvent absorption has been followed in injection-molded samples for 13 solvents in cyclic olefinic copolymer (COC), 4 solvents in two different grades of polycarbonate (PC), and 2 solvents in the terpolymer acrylonitrile/butadiene/styrene (ABS). It was discovered that a surface resistance to absorption was significant in 19 of these 23 cases. Approximate surface mass transfer coefficients and approximate diffusion coefficients were determined where possible. There is no surface resistance to absorption where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…2) show an initial time lag period where no important weight gain is observed. The same type of ''S"-shape curves has been observed in systems where the surface resistance becomes important (Nielsen and Hansenm, 2005). k was estimated experimentally from the uptake curves as the point where a back extrapolation line, from the middle points of the curve, crosses the x-axis and q s0 was zero for all the simulations.…”
Section: Resultsmentioning
confidence: 54%
“…2) show an initial time lag period where no important weight gain is observed. The same type of ''S"-shape curves has been observed in systems where the surface resistance becomes important (Nielsen and Hansenm, 2005). k was estimated experimentally from the uptake curves as the point where a back extrapolation line, from the middle points of the curve, crosses the x-axis and q s0 was zero for all the simulations.…”
Section: Resultsmentioning
confidence: 54%
“…The solvent activation process by exposure of polymers to solvent vapour involves the adsorption/absorption of solvent molecules onto the polymer surface, passage through the surface, and nally distribution in the bulk. 25 Due to Brownian motion, solvent molecules randomly hit the polymer surface.…”
Section: Surface Activationmentioning
confidence: 99%
“…A process of solvent vapour infusion, however, has been reported to show non-reproducible bonding behaviour 15,20,23 possibly due to the effect of a surface resistance. 25 Wallow et al 20 also mention when "some of the plastic components are not fully exposed to the permeanta surface layer or "skin" develops -[which] interferes with the bonding process [making it] necessary for all the plastic components to be bonded to receive at least a brief exposure to the permeant in order to break through this surface layer". Nevertheless, the infusion process has been shown to be successful for PMMA and COP/COC chip production even aer exposure of just one component and only for a few minutes of activation.…”
Section: Introductionmentioning
confidence: 99%
“…), but it dissolves in various nonpolar solvents (various alkanes, toluene, etc.). A recent study [41] discusses the surface adsorption of solvents on COC and various other polymers. Dissolution tests indicated that solvents like toluene and heptane completely dissolved COC in a short time.…”
Section: Sealing By Warm Lamination Following Controlled Plasticizingmentioning
confidence: 99%